Karakteristik Karakteristik Epidemiologi Pasien COVID-19 di Rawat Inap RSU Royal Prima Marelan Tahun 2021 - Farma Kasih Br Hutauruk (STIKES ADVAITA MEDIKA TABANAN, 2023)
COVID-19 is one of the infectious diseases originating from a new type of corona virus known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and has become a concern because it has caused a lot of morbidity and mortality. This study aims to describe the general characteristics of COVID-19 patients at RSU Royal Prima Marelan, such as gender, age, occupation, domicile, length of stay, clinical symptoms, co-morbidities, patient criteria, and mortality. This research method uses a descriptive quantitative approach. The study population was all COVID-19 patients treated at RSU Royal Prima Marelan in 2021 with a sample of 125. The results showed that COVID-19 was more common in the male group of 68 (54%). With age 20-60 years 88 (70%). Working status 70 (56%). A total of 76 people are currently married (61%). Non-Marelan domicile (89%). Length of treatment 1 week 82 (66%) with criteria suspect 81 (65%). The mortality rate for COVID-19 patients is 12%. Clinical symptoms experienced were cough (94%), shortness of breath (90%), and fever (89%). With comorbid hypertension 27 (22%), DM 6 (5%), asthma 7 (6%). In conclusion, the characteristics of COVID-19 patients mostly occur in the male group with an age range of 20-60 years, symptoms that arise such as fever, shortness of breath and cough with comorbid hypertension, DM and asthma. Mortality was recorded at 12% with hypertension as the highest comorbid disease